Productive performance and egg physical characteristics of Tufted Creole and Marans hens: Productive performance and egg physical characteristics of Tufted Creole and Marans hens (Agro Productividad, 2020)
Objective: The present study was conducted to evaluate the productive performance and the egg physical characteristics of two backyard-type breeds of birds.Design/methodology/approach: Tufted Creole (13 hens and a rooster) and Marans (13 hens and a rooster) hens were used in this study. Live body weight, feed intake, egg production, egg weight, egg length and egg width were measuredweekly for eight weeks. Collected data were analyzed using a two-way variance analysis; the main factors were breed, week, and their interaction.Results: Marans hens were heavier and had higher feed intake than Tufted Creole (TCH) (P